1982
DOI: 10.1021/jo00133a013
|View full text |Cite
|
Sign up to set email alerts
|

.sigma.-Naphthoquinodimethanes and .sigma.-phenanthroquinodimethanes. Isoindene-related species

Abstract: Three isoindene-related naphthoquinodimethane and phenanthroquinodimethane species were synthesized and trapped with 4-phenyl-l,2,4-triazoline-3,5-dione. They are 2,2-dimethyl-2/f-benz[e]indene (3), 2,2-dimethyl-2R-benz [/]indene (4), and 2,2-dimethyl-9H-cyclopenta[6]phenanthrene (10). Compound 3 could be isolated and characterized by NMR. The effect of solvent on the bisacylation of naphthalene and phenanthrene by dimethylmalonyl chloride is discussed. Also the use of the Vilsmeier reagent generated from PBr3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Its reaction with tribromophosphane furnished the bromo derivative 7 in 81% yield. 19 8 was finally afforded in 62% yield after lithiation of CPDT 16b,20 at position 4, followed by a reaction with 7.…”
Section: Resultsmentioning
confidence: 99%
“…Its reaction with tribromophosphane furnished the bromo derivative 7 in 81% yield. 19 8 was finally afforded in 62% yield after lithiation of CPDT 16b,20 at position 4, followed by a reaction with 7.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of less-strained six-membered ring isomer 15 over the other possible five-membered ring isomers 16 and 17 in the Friedel−Crafts (FC) reaction is expected to be thermodynamically more favorable. However, Dolbier et al have shown that the solvent has a dramatic effect on the product distribution in FC reaction of this type of substrates . The compound 15 was characterized by its symmetrical 1 H and 13 C NMR spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…However, Dolbier et al have shown that the solvent has a dramatic effect on the product distribution in FC reaction of this type of substrates. 14 The compound 15 was characterized by its symmetrical 1 H and 13 C NMR spectral data. The other two isomers were also identified on the basis of 1 H NMR spectral data.…”
Section: Resultsmentioning
confidence: 99%